Investigation of groundwater potential in Melaka district of Malaysia - Shirazi, S.M.; Hasen, I.; Sholichin, M. (2011)
The paper assesses groundwater quality and productivity in Melaka, Peninsular Malaysia. 238 data set shallow boreholes, 20 data set deep boreholes were collected and continuous pumping test data were used to determine productivity of the aquifers. 68 water samples were tested for water quality. The productivity of the wells and the characteristics of the aquifer were evaluated by pumping test using both the constant discharge rate and steps drawdown methods. The potential of shallow groundwater is low with average discharge <5 m3/hour. The potential of deep groundwater is high category with average discharge > 20 m3/hour. The results show that 32% (538 km2) from total area of Mel aka district (1650 km ) is low potential categories, 56% (922 km2) is moderate and 12% (194 km2) is high. Based on the chemical data, the quality of deep aquifer is fresh. Therefore, it is available for drinking water with minimum treatment.